Analisis kemampuan literasi digital siswa pada mata pelajaran IPAS kelas V dalam penggunaan aplikasi quizizz - Dewi Anggi Agustin; Ratna Sari Dewi; Sigit Setiawan (Trihayu: Jurnal Pendidikan Ke-SD-an, 2026)
This study aims to analyze the digital literacy skills of fifth-grade students at Kebon Elementary School (SDN Kebon) in using the Quizizz application in science subjects. Educational challenges in the Society 5.0 era demand the use of technology and digital literacy competencies in learning. The use of digital platforms such as the Quizizz application is a solution to replace conventional methods, which are considered ineffective and inefficient in the digital age. This study used a qualitative method with a phenomenological approach and was conducted at Kebon Elementary School, Serang Regency, from March to October 2025. Data collection was carried out using observation, interviews, and documentation techniques, with data analysis using the Miles & Huberman interactive model. The study concluded that the learning planning process and the design of Quizizz-based evaluation questions were carried out systematically and structured. The implementation of learning and formative assessment using Quizizz were effective and efficient. Students' digital literacy skills were categorized as good. Students were able to demonstrate four digital literacy skills: Digital Skills, Digital Culture, Digital Ethics, Digital Safety.